Optimizing Adaptive Neuro Fuzzy Inference System (Anfis) With Dragonfly Algorithm For Cardiovascular Disease - Jinjiri, Wada Mohammed (2023)
Cardiovascular disease (CVD) remains a great concern in the field of healthcare. It is responsible for the highest mortality rate leading cause of death worldwide. This research utilizes an Adaptive neuro-fuzzy inference system (ANFIS) and addresses the problem of topology and parametric configurations that lead to the prediction error for CVD.